PENGARUH KEADILAN ORGANISASIONAL TERHADAP PERILAKU KERJA INOVATIF DENGAN KEPERCAYAAN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI PADA KARYAWAN GRAND INNA PADANG HOTEL - Jeanrie Kristiani Anggriani Taime; Mega Asri Zona (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This research analyzed: (1) The influence of organizational justice on innovative work behavior (2) The influence of organizational justice on organizational trust (3) The influence of organizational trust on innovative work behavior (4) The influence of organizational justice on innovative work behavior with organizational trust as mediating variable. This research is descriptive causative research. The population in this research is all employees in the Grand Inna Padang Hotel. The number of samples was determined by purposive sampling technique. This research analyzed using regression with SPSS. Regarding the partial mediation model proposed, the data confirm the relationship set out in the hypothesis. The hypothesis testing founds: (1) Organizational justice has positive and significant influence on innovative work behavior in Grand Inna Padang Hotel (2) Organizational justice has a positive and significant effect on organizational trust in Grand Inna Padang Hotel (3) Organizational trust has positive and significant influence on innovative work behavior in Grand Inna Padang Hotel (4) Organizational trust mediated the relationship between organizational justice and innovative work behavior in Grand Inna Padang Hotel. This analysis highlights the positive influences for organizational justice and organizational trust on innovative work behavior.